BrewEase: Coffee Shop Order Management System - Mohd Arifin, Mashitah; Selamat, Norhanim (Applied Information Technology And Computer Science, 2026)
The growing coffee shop industry demands efficient systems to enhance service and streamline operations. BrewEase is a web-based Coffee Shop Order Management System developed using PHP, MySQL, JavaScript, and Tailwind CSS within the MVC architecture. It aims to improve customer experience, automate orders, and integrate a loyalty points program. Key features include menu and payment management, as well as sales analytics and reporting. Compared to manual processes and generic POS systems, BrewEase offers improved order accuracy, faster service, and customer retention through its loyalty program. Developed using an iterative methodology, the system is scalable and user-friendly for customers, cashiers, and managers. BrewEase demonstrates how tailored digital solutions can enhance operational efficiency, user satisfaction, and business performance.